Topografier, klichéer och verkligheter - Öhman, Anders (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1999)
In this essay I discuss literary topography in relation to the notion of reality and to the cliché. I argue that mapping is essential to writing, even if it in literature means to deal with textual topos. J. Hillis Miller has shown in his book Topographies that the relation between literary topography and reality is an almost unsolvable paradox. That is, there is certainly an external terrain outside the text, but it is through the text that this terrain comes into existence. And without a reality outside the text, there wouldn’t be any need to continue the search for the right angle to view this reality, and the driving force behind the creative act would be lost. I then compare two contemporary Swedish authors and their relationship towards topography. The topography in P. O. Enquist’s novels is unique and very personal, while the novels of Ulf Lundell are dealing with topos that are widespread and collectively known. But in either way, in order to be meaningsful to their group of readers, respectively, their topos have to be a kind of loci communes — commonplaces — or clichés. This makes it possible to understand the cliché in a better and less pejorative way. All topos are in some way clichés, even if they are aimed at and can only be understood by an exclusive group of readers. This kind of topographic reading of the literary text is also what we meet in the hypertext at the internet.